2008
DOI: 10.1248/jhs.54.432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Therapeutic Effects Recombinant Human Acidic and Basic Fibroblast Growth Factors in Wound Healing in Diabetic Patients

Abstract: To explore an optimal improvement of diabetic wound healing we have comparatively studied the effects of recombinant human acidic and basic fibroblast growth factors (rhaFGF and rhbFGF) on the healing impaired skin wounds in diabetic patients. Before using rhaFGF in diabetic patients, its pharmacokinetic features and possible toxic effects were evaluated using a rabbit model. For the 139 diabetic patients, 25% of them were divided into the group to receive topical rhbFGF daily at the dose of 100 U/0.1 ml/cm 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…22) Supplementation of exogenous FGFs attenuated diabetes-caused neuronal and gastric tissue damage. 23,24) We have performed experimental and clinical studies, demonstrating that topical application of recombinant human acidic FGF (rhaFGF) and basic FGF (rhbFGF) promoted the healing of skin ulcer in diabetic patients, 25) and diabetic rats. 26) Cardiac infarction and dysfunction are life-threatening diseases.…”
mentioning
confidence: 99%
“…22) Supplementation of exogenous FGFs attenuated diabetes-caused neuronal and gastric tissue damage. 23,24) We have performed experimental and clinical studies, demonstrating that topical application of recombinant human acidic FGF (rhaFGF) and basic FGF (rhbFGF) promoted the healing of skin ulcer in diabetic patients, 25) and diabetic rats. 26) Cardiac infarction and dysfunction are life-threatening diseases.…”
mentioning
confidence: 99%
“…We did not include non-diabetic group in this study since each of the approach used in the combination has been used extensively to non-diabetic animals. 19,33,[39][40][41] In these previous studies, application of the exogenous growth factors or Zn did not always stimulate the wound healing process, for which one of the reasons is because normal tissue is not defect for these growth factors or nutrients such as Zn. 42) Diabetic induction by STZ and the full-thickness skin wound for the diabetic rats was made as described in the pilot study.…”
Section: Methodsmentioning
confidence: 93%
“…19) For this end, diabetic and age-matched nondiabetic (control) rats were anesthetized with 5% Chloral Hydrate (0.5 ml/kg body weight) and depilated using 8% sodium sulfide. A round marker (diameter 2.4 cm, 4.52 cm 2 ) was made on the back of rats with methylrosanilinium chloride.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When kanamycin selection was applied, authors reported similar TEs: 9% (8), 9.9% (33). However, in publications where the main purpose is development of transgenic tomato plants producing valuable recombinant proteins, the TE was not mentioned (26,53,61).…”
Section: Genetic Transformation Selection and Regenerationmentioning
confidence: 99%